Talaromyces marneffei infection relapse presenting as osteolytic destruction followed by suspected nontuberculous mycobacterium infection during 6 years of follow-up: A case update. (April 2020) - Liang, Xiaona; Si, Lu; Li, Yinghua; Zhang, Jianquan; Deng, Jingmin; Bai, Jing; Li, Meihua; He, Zhiyi
Highlights: HIV-negative Chinese woman experienced T. marneffei infection relapse. She was diagnosed with NTM coinfection and responded well to anti-NTM treatment. T. marneffei infection with osteolytic lesions needs prolonged antifungal therapy. Non-HIV patients with T. marneffei need to test anti-IFN-γ autoantibody. Anti-IFN-γ autoantibody increases infection risk, commonly T. marneffei and NTM. Abstract: Talaromyces (formerly Penicillium ) marneffei, a dimorphic fungus, is the most common opportunistic pathogen in human immunodeficiency viruses (HIV)-positive patients, but it rarely appears in HIV-negative individuals. Previously, in 2014, we reported the case of an HIV-negative Chinese woman with disseminated T. marneffei infection within an osteolytic lesion. Subsequently, she was followed up for 6 years, and we present an updated report of her clinical condition during the follow-up period. She presented with T. marneffei infection relapse and nontuberculous mycobacterium (NTM) infection. Laboratory tests showed anti-interferon-gamma (anti-IFN-γ) autoantibody-positive. Antifungals and anti-NTM treatment successfully improved her symptoms and laboratory results. This case highlights the type of infectious diseases that occurs as a result of immunodeficiency syndrome associated with anti-IFN-γ autoantibody.